BLAH - (:unkn) unknown (My University, 2020)
Η Μεταπτυχιακή Εργασία διερευνά το σύστημα της Γλώσσας ως δημόσιο υλικό και ως αναλυτικό εργαλείο που δίνει σχήμα σε κάθε μοντέλο κοινωνικής βαρύτητας. Πιο συγκεκριμένα διερευνά τις σχέσεις μεταξύ γλώσσας και εξουσίας, γλώσσας και πραγματικότητας. Το θεωρητικό μέρος αποτελείται από τρεις ενότητες i.Βαρύτητα ii. Αέρας iii. Γλώσσα. Το κύριο θέμα είναι το σύστημα της γλώσσας και οι λειτουργίες της. Οι άλλες δύο ενότητες λειτουργούν ως συσχετίσεις «ομοιότητας υπεράνω εμφάνισης» ή ως οι δύο αντίθετοι πόλοι στους οποίους πλοηγούμε ώστε να καταλάβω. Το καλλιτεχνικό μέρος αποσκοπεί στο να στρέψει την προσοχή από τη γλώσσα ως δομικό σύστημα, στην άλογη φωνή: το πρωταρχικό σώμα κάθε γλωσσικής σημασίας. Και να παρατηρήσει το φαινόμενο του ομιλούντος υποκειμένου απαλλαγμένο από τις γλωσσικές συμβάσεις.

As a terrestrial being, I experience the Earth through my own corporeality. Gravity is the main source of my identity and shapes the way I construct the world and myself. The same does language - the arbitrary system through which I express myself, extract meaning, give myself an identity , interact with my fellow human beings and shape my reality. Gravity and language are the most present concepts of force(power) that I experience as physical and social materiality. One belongs to physics and the other to metaphysics - both predominantly dominant. The attraction of the earth prevents the mysterious universe from swallowing me and creates the frame in which I exist. Language does the same by offering the ontological framework through which I distribute and categorize this enormous continuum which I call reality but at the same time remains an arbitrary conventional system which is a derivative from its own self. Air is the main element of speech, but also the element that encompases its own negation and shapes my relationship to the absent. It functions as a means by which thought becomes a voice and acquires its immaterial materiality or as the interval between gravity and antigravity, logic and nonsense, and here opens the discussion of what makes a subject and what makes an object. According to Michel Serres, the noise of the vocal expression that drives the mouth is suppressed by its linguistic functions. The social and linguistic structure of language comes to tune the mouth, locating it in a grammar of expressions, which is mainly associated with the function of speech. Gilles Deleuze in the "Manifesto of Nonsense" in 1960 presented the case of nonsense as the ultimate being of language, reaching the same conclusion as many other thinkers. Russian Futurism, Dadaism, early Avant Garde, Postmodernism, Post-structuralism, etc. insisted on finding ways to liberate language from the structures of preconceived meaning or even eliminate, totally, every linguistic sense. What they all suggest is to take a closer look to the nonsensical vocality, the primary body of every linguistic signification, the messy basis of the wording, the noise underneath the speech. But this is a process that emboldens one in negotiating the intensities of being a subject and perhaps the approach of the speaking subject requires a deeper creativity and a certain amount of playfulness and lightness in order to enable new types of reflection and understanding.
Keywords: γλωσσικό σύστημα, άλογη φωνή, αέρας, βαρύτητα, λόγος, ομιλούν υποκείμενο, σημαίνον/σημαινόμενο, έκφραση, επικοινωνία, σημασιοδότηση, εξουσία